Global maximum power point tracking method for photovoltaic systems using Takagi-Sugeno fuzzy models and ANFIS approach - Hadjidj, N.; Benbrahim, M.; Ounnas, D.; Mouss, L. H. (Національний технічний університет "Харківський політехнічний інститут", 2025)
A new global maximum power point tracking (GMPPT) control strategy for a solar photovoltaic (PV) system, based on the combination of Takagi-Sugeno (T-S) fuzzy models and an ANFIS, is presented. The novelty of this paper lies in the integration of T-S fuzzy models and the ANFIS approach to develop an efficient GMPPT controller for a PV system operating under partial shading conditions. Purpose. The new GMPPT control strategy aims to extract maximum power from the PV system under varying weather conditions or partial shading. Methods. An ANFIS algorithm is used to determine the maximum voltage, which corresponds to the actual maximum power point, based on PV voltage and current. Next, the nonlinear model of the PV system is employed to design the T-S fuzzy controller. A reference model is then derived based on the maximum voltage. Finally, a tracking controller is developed using the reference model and the T-S fuzzy controller. The stability of the overall system is evaluated using Lyapunov’s method and is represented through linear matrix inequalities expressions. The results clearly demonstrate the advantages of the proposed GMPPT-based fuzzy control strategy, showcasing its high performance in effectively reducing oscillations in various steady states of the PV system, ensuring minimal overshoot and a faster response time. In addition, a comparative analysis of the proposed GMPPT controller against conventional algorithms, such as Incremental Conductance, Perturb & Observe and Particle Swarm Optimization, shows that it offers a fast dynamic response in finding the maximum power with significantly less oscillation around the maximum power point.

Представлена нова глобальна стратегія відстеження точки максимальної потужності (GMPPT) для сонячної фотоелектричної (PV) системи, заснована на комбінації нечітких моделей Такагі-Сугено (T-S) і ANFIS. Новизна статті полягає в інтеграції нечітких моделей T-S і підходу ANFIS для розробки ефективного контролера GMPPT для PV системи, що працює в умовах часткового затінення. Мета. Нова стратегія контролю GMPPT спрямована на отримання максимальної потужності від PV системи за змінних погодних умов або часткового затінення. Методи. Алгоритм ANFIS використовується для визначення максимальної напруги, яка відповідає фактичній точці максимальної потужності, на основі PV напруги та струму. Далі нелінійна модель PV системи використовується для розробки нечіткого контролера T-S. Потім на основі максимальної напруги виводиться еталонна модель. Нарешті, контролер стеження розроблено з використанням еталонної моделі та нечіткого контролера T-S. Стійкість системи в цілому оцінюється за допомогою методу Ляпунова і представляється у вигляді лінійних матричних нерівностей. Результати чітко демонструють переваги запропонованої стратегії нечіткого керування на основі GMPPT, демонструючи її високу продуктивність щодо ефективного зменшення коливань у різних сталих станах PV системи, забезпечуючи мінімальне перерегулювання та швидший час відгуку. Крім того, порівняльний аналіз пропонованого контролера GMPPT із звичайними алгоритмами, такими як Incremental Conductance, Perturb and Observe та Particle Swarm Optimization, показує, що він пропонує швидку динамічну реакцію у пошуку максимальної потужності зі значно меншими коливаннями навколо точки максимальної потужності.
Keywords: photovoltaic system; maximum power point tracking; Takagi-Sugeno fuzzy model; linear matrix inequalities; фотоелектрична система; відстеження точки максимальної потужності; нечітка модель Такагі-Сугено; лінійні матричні нерівності